PENGETAHUAN DAN TINDAKAN REMAJA PUTRI TENTANG PEMERIKSAAN PAYUDARA SENDIRI - Sri Legawati; Sri Rezeki; Efi Irwansyah Pane; Nasywa Azra Zeina Sirait (Jurnal Keperawatan Dan Kesehatan Holistik, 2026)
Breast cancer ranks first in terms of the number of cancers in Indonesia and is one of the leading causes of cancer deaths. Approximately 43% of cancer deaths can be prevented if patients regularly perform early detection through breast self-examination (SADARI) and avoid risk factors that cause cancer. The purpose of this study was to determine the behavior of adolescent girls regarding SADARI (Breast Self-Examination). The research type was a descriptive survey. The population in this study was all 273 12th-grade female adolescents attending MAN Asahan. The sample was determined using the Yount formula (1999) using a purposive sampling technique, meaning sampling is based on certain considerations made by the researcher, based on previously known characteristics or traits of the population. The sample size in this study was 27 12th-grade female adolescents at MAN Asahan. The results of the measurement of adolescent knowledge about breast self-examination fell into the good category with a total score of 8.36 (92.88%), and the measurement of actions fell into the good category with a total score of 6.46 (77.77%). The final conclusion of the study on the knowledge and practices of adolescent girls regarding breast self-examination (BSE) at Asahan State Islamic Senior High School (Islamic Senior High School) is that it falls into the good category (85.29%). There is a significant relationship between knowledge level and BSE behavior. Adolescent girls with good knowledge tend to have positive attitudes and better practices in performing BSE. Given the increasing importance of BSE for adolescent girls, schools should incorporate BSE into extracurricular curricula through School Health Program activities. As a smart generation, adolescent girls should be proactive in seeking accurate and reliable information about reproductive health, including BSE.